Three strategies for attaining legitimacy in policy knowledge: Coherence in identity, process and outcome. (11th January 2018) - Williams, Kate
Abstract : At a time when truth and facts are highly contested, understanding how knowledge gains legitimacy is crucial. Creating valuable policy knowledge involves navigating 'a space between fields', where actors and ideas from different social worlds come into play. This article outlines a novel set of strategies for attaining legitimacy within this space. Drawing on mixed‐methods analysis of interview and publication data from 12 development research organizations, the article argues that legitimacy centres around three primary types of 'coherence'. Coherence in identity is the demonstration of 'proper' goals via negotiation of organizational and individual identity. Coherence in process is the demonstration of 'proper' processes through maintenance of independence, integrity and transparency. Coherence in outcome is the demonstration of 'proper' outcomes via creation of the 'right' products, audience and impact. Mastery of these three areas makes possible the production of credible, distinctive and significant knowledge.